Associations between Neighborhood Resources and Physical Activity in Inner City Minority Children - Galvez, Maida P. (2013)
OBJECTIVE: The role of neighborhood physical activity resources on childhood physical activity level is increasingly examined in pediatric obesity research. We describe how availability of physical activity resources varies by individual and block characteristics and then examine its associations with physical activity levels of Latino and black children in East Harlem, New York City. METHODS: Physical activity resource availability by individual and block characteristics were assessed in 324 children. Availability was measured against four physical activity measures: average weekly hours of outdoor unscheduled physical activity, average weekly metabolic hours of scheduled physical activity, daily hours of sedentary behavior and daily steps. RESULTS: Physical activity resource availability differed by race/ethnicity, caregiver education and income. Presence of one or more playgrounds on a child’s block was positively associated with outdoor unscheduled physical activity (OR=1.95, 95% confidence interval 1.11–3.43). Presence of an afterschool program on a child’s block was associated with increased hours of scheduled physical activity (OR=3.25, 95% confidence interval 1.41–7.50) and decreased sedentary behavior (OR=3.24, 95% confidence interval 1.30–8.07). The more resources a child had available, the greater the level of outdoor unscheduled physical activity (p for linear trend=.026). CONCLUSIONS: Neighborhood physical activity resource availability differs by demographic factors, potentially placing certain groups at risk for low physical activity level. Availability of select physical activity resources was associated with reported physical activity levels of East Harlem children but not with objective measures of physical activity.